Preparation of Biodiesel from Higher FFA Containing Castor Oil - Khan, Maksudur R.; Ferdous, Kaniz; Deb, Anjan; Ferdous, Jannatul; Uddin, M. Rakib; Islam, M. A. ((IJSER.org) - International Journal of Scientific & Engineering Research, 2013)
Current study reveals the production of biodiesel from non-edible oil such as castor oil (Ricinus Communis L.). Oil was extracted from seed by mechanical press method. Various properties of the raw oil were measured by standard methods. Free Fatty Acid (FFA) content of the oil was found as 13.6% and kinematic viscosity was 253 mm²/s. Base catalyzed transesterification is widely used for biodiesel production than acid catalyzed transesterification due to its faster kinetics. But if the FFA content of the oil is higher than 2wt% then base catalyzed transesterification is not feasible. Hence, a two-step method, acid catalyzed esterification followed by base catalyzed transesterification was applied for the production of biodiesel from castor oil. After the esterification reaction FFA content of the oil was reduced below 2wt% which makes it suitable for base catalyzed transesterification. The reaction parameters for esterification and transesterification were optimized. 1 NMR was studied for both oil and biodiesel. Finally, various properties of produced biodiesel from castor oil, such as specific gravity, viscosity, FFA, cloud point, flash point, saponification value, etc. were measured and compared with standard diesel and biodiesel properties.